Multiple Sclerosis: Improved Detection of Active Cerebral Lesions With 3-Dimensional T1 Black-Blood Magnetic Resonance Imaging Compared With Conventional 3-Dimensional T1 GRE Imaging. Issue 1 (January 2018) - Sommer, Nora N.; Saam, Tobias; Coppenrath, Eva; Kooijman, Hendrik; Kümpfel, Tania; Patzig, Maximilian; Beyer, Sebastian E.; Sommer, Wieland H.; Reiser, Maximilian F.; Ertl-Wagner, Birgit; Treitl, Karla M.
Abstract : Objectives: The aim of this study was to assess the diagnostic accuracy of a modified high-resolution whole-brain three-dimensional T1-weighted black-blood sequence (T1-weighted modified volumetric isotropic turbo spin echo acquisition [T1-mVISTA]) in comparison to a standard three-dimensional T1-weighted magnetization-prepared rapid gradient echo (MP-RAGE) sequence for detection of contrast-enhancing cerebral lesions in patients with relapsing-remitting multiple sclerosis (MS). Materials and Methods: After institutional review board approval and informed consent, 22 patients (8 men; aged 31.0 ± 9.2 years) with relapsing-remitting MS were included in this monocentric prospective cohort study. Contrast-enhanced T1-mVISTA and MP-RAGE, both with 0.8 mm 3 resolution, were performed in all patients. In a substudy of 12 patients, T1-mVISTA was compared with a T1-mVISTA with 1.0 mm 3 resolution (T1-mVISTA_1.0). Reference lesions were defined by an experienced neuroradiologist using all available sequences and served as the criterion standard. T1-mVISTA, T1-mVISTA_1.0, and MP-RAGE sequences were read in random order 4 weeks apart. Image quality, visual contrast enhancement, contrast-to-noise-ratio (CNR), diagnostic confidence, and lesion size were assessed and compared by Wilcoxon and Mann-Whitney U tests. Results: Eleven of 22 patients displayed contrast-enhancing lesions. Visual contrast enhancement, CNR, and diagnostic confidence of contrast-enhancing MS lesions were significantly increased in T1-mVISTA compared with MP-RAGE ( P < 0.001). Significantly more contrast-enhancing lesions were detected with T1-mVISTA than with MP-RAGE (71 vs 39, respectively; P < 0.001). With MP-RAGE, 25.6% of lesions were missed in the initial reading, whereas only 4.2% of lesions were missed with T1-mVISTA. Increase of the voxel volume from 0.8 mm to 1.0 mm isotropic in T1-mVISTA_1.0 did not affect the detectability of lesions, whereas scan time was decreased from 4:43 to 1:55 minutes. Conclusions: Three-dimensional T1-mVISTA improves the detection rates of contrast-enhancing cerebral MS lesions compared with conventional 3D MP-RAGE sequences by increasing CNR of lesions and might, therefore, be useful in patient management.